Psychological Outcomes and Associated Factors Among the International Students Living in China During the COVID-19 Pandemic - Alam, Md. Dhedharul; Lu, Jing; Ni, Li; Hu, Shaohua; Xu, Yi (Frontiers in Psychiatry, 2021)
Background: The emergence of COVID-19 has created a severe mental health problem for international students living in China. Despite the little information on the psychological impact on international students, we aimed to assess the psychological outcomes and associated factors among international students currently living in China during the COVID-19 pandemic. Methods: An online cross-sectional survey was conducted from May 28, 2020, to June 12, 2020, on 402 full-time international students across 26 provinces in China. The frequency of symptoms of depression, anxiety, stress, insomnia, psychological distress, loneliness, and fear was assessed with the English versions of the DASS-21, ISI, K6, UCLA-LS, and FCV-19S scales, respectively. Results: The prevalence of symptoms of depression (73.4%), anxiety (76.6%), stress (58.5%), insomnia (77.6%), psychological distress (71.4%), loneliness (62.4%), and fear (73.1%) among international students during the COVID-19 pandemic. The prevalence of moderate to extremely severe symptoms of all psychological outcomes was significantly associated with 26-30 years old students, students who lived with roommates, and students who stayed in China shorter than two years. Participants in the central region were reported significantly moderate to extremely severe symptom levels of all the psychological outcomes except fear symptoms. Univariate analysis indicated that a significant association of all psychological outcomes was found among 26-30 years old students and students who stayed in China shorter than two years. Multivariate analysis showed that Engineering, Business, Social Sciences & Law, and Language students were significantly associated with the symptoms of depression, anxiety, insomnia, and fear. Participants staying in China for a shorter than two years were associated with a higher risk of all psychological outcomes except psychological distress and loneliness symptoms. Conclusions: We found a higher prevalence of psychological outcomes and risk factors among international students during the COVID-19 pandemic. We immediately appealed to university authorities, mental health professionals, and government officials to provide mental health interventions and strategies for their international students, particularly young, central region students living with roommates, different study backgrounds, and short time staying during the pandemic.